APLIKASI KOAGULAN CAIR HASIL EKSTRAKSI 0,4 MOL H2SO 4 UNTUK PENGOLAHAN AIR GAMBUT - Catrain Susanty; Muhdarina '; Akmal Mukhtar (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Clay is an abundant natural product that has been used in various fields, one of them as a coagulant in water treatment. Cengar clay contains aluminium and iron that can be extracted to be liquid coagulant. The liquid coagulant was prepared through extraction of 500o C calcined Cengar clay by 0,4 mol of sulfuric acid at various temperatures (30,60, and 100o C) and extraction times (1, 2, and 3 hours). These coagulants were applied to coagulation process of peat water. Several parameters of peat water that were analyzed are turbidity, total dissolve solid (TDS), and total suspended solid (TSS). The turbidity result was compared to PERMENKES RI No. 416/MENKES/PER/IX/1990 “About Requirement and Water Quality Control”, whereas TDS and TSS were compared to Government Regulation No. 82 of 2001 “About Water Quality Treatment and Water Pollution Control” class I (raw drinking water). The result showed that liquid coagulants can fix all of peat water parameters that were analyzed. The optimum coagulant was K 60-3, made through extraction at 60o C for 3 hours, with removal percentage of turbidity was 82,69%; TSS 94,06%, and TDS 84,75%.